Lamivudine modulates the expression of neurological impairment-related genes and LINE-1 retrotransposons in brain tissues of a Down syndrome mouse model - Borgognone, Alessandra; Casadellà, Maria; Martínez de Lagrán, María; Paredes, Roger; Clotet, Bonaventura; Dierssen, Mara; Elizalde-Torrent, Aleix (Frontiers in Aging Neuroscience, 2024)
Elevated activity of retrotransposons is increasingly recognized to be implicated in a wide range of neurodegenerative and neurodevelopmental diseases, including Down syndrome (DS), which is the most common chromosomal condition causing intellectual disability globally. Previous research by our group has revealed that treatment with lamivudine, a reverse transcriptase inhibitor, improved neurobehavioral phenotypes and completely rescued hippocampal-dependent recognition memory in a DS mouse model, Ts65Dn. We hypothesized that retrotransposition rates would increase in the Ts65Dn mouse model, and lamivudine could block retrotransposons. We analyzed the differentially expressed long interspersed element-1 (LINE-1 or L1) mapping on MMU16 and 17, and showed for the first time that retrotransposition could be associated with Ts65Dn's pathology, as misregulation of L1 was found in brain tissues associated with trisomy. In the cerebral cortex, 6 out of 26 upregulated L1s in trisomic treated mice were located in the telomeric region of MMU16 near Ttc3, Kcnj6, and Dscam genes. In the hippocampus, one upregulated L1 element in trisomic treated mice was located near the Fgd4 gene on MMU16. Moreover, two downregulated L1s rescued after treatment with lamivudine were located in the intronic region of Nrxn1 (MMU17) and Snhg14 (MMU7), implicated in a variety of neurodegenerative disorders.To gain further insight into the mechanism of this improvement, we here analyzed the gene expression profile in the hippocampus and cerebral cortex of trisomic mice treated and no-treated with lamivudine compared to their wild-type littermates. We found that treatment with lamivudine rescued the expression of 24% of trisomic genes in the cortex (located on mouse chromosome (MMU) 16 and 17) and 15% in the hippocampus (located in the human chromosome 21 orthologous regions), with important DS candidate genes such as App and Ets2, rescued in both regions.